2021
DOI: 10.21037/qims-20-1254
|View full text |Cite
|
Sign up to set email alerts
|

Brain neurometabolites differences in individuals with subjective cognitive decline plus: a quantitative single- and multi-voxel proton magnetic resonance spectroscopy study

Abstract: Background: Subjective cognitive decline plus could be an extremely early phase of Alzheimer's disease; however, changes of N-acetylaspartate, myoinositol, and N-acetylaspartate/myoinositol is still unknown at this stage. This study aimed to explore brain neurometabolic alterations in patients with subjective cognitive decline plus using quantitative single-voxel and multi-voxel 1H-magnetic resonance spectroscopy.Methods: A total of 91 participants were enrolled and underwent a GE 3.0-T magnetic resonance imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
0
5
1
Order By: Relevance
“…In our study, we demonstrated that an increasing annualized MDASI delayed score (worsening) was associated with a decline in annualized NAA in the medial frontal region, which is consistent with earlier research. [ 16 , 25 , 26 ] Contrary to earlier assumptions, our study and another study demonstrated that Cr was not stable in patients who received chemotherapy. [ 16 ] MRS data are commonly presented either as concentration ratio relative to creatine (assuming that creatine is not affected by the pathology) or as a concentration utilizing the water signal obtained from the corresponding volume of interest as a reference.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, we demonstrated that an increasing annualized MDASI delayed score (worsening) was associated with a decline in annualized NAA in the medial frontal region, which is consistent with earlier research. [ 16 , 25 , 26 ] Contrary to earlier assumptions, our study and another study demonstrated that Cr was not stable in patients who received chemotherapy. [ 16 ] MRS data are commonly presented either as concentration ratio relative to creatine (assuming that creatine is not affected by the pathology) or as a concentration utilizing the water signal obtained from the corresponding volume of interest as a reference.…”
Section: Discussioncontrasting
confidence: 99%
“…83 Relatively few papers in this review calculated Cr concentration and most did not report significant results. Where differences were found, Cr was found to be lower in patient groups (AD, MCI and DLB) across a range of regions 51,54,77,94 but higher in older controls in 'at-risk' cohorts. 83,86 These results underscore the problem of using Cr as a reference region, especially within dementia research, as the relationship of Cr with disease and age is unclear.…”
Section: Discussionmentioning
confidence: 92%
“…47,51 Ten studies considered Cr (or tCr) as a metabolite of interest: seven reported no significant results 26,29,32,42,46,50,53 ; one found lower ACC and PCC Cr in AD and MCI groups compared with controls but no significant difference between AD and MCI groups 51 ; another found lower left dorsal thalamic tCr in MCI compared with controls. 54 A functional MRS study found that changes in PCC tCr between three stimulation conditions differentiated between AD, MCI and controls with relatively high sensitivity and specificity (highest for AD versus controls, sensitivity 87.5, specificity 63.89). 94…”
Section: Summary Of Findings: Ad Ad/mci MCI Studiesmentioning
confidence: 99%
“…2021 ). However, few studies have performed direct pathological investigations to analyze the histology underlying brain volume changes in VMCI ( Yang, Wan, et al. 2021 ).…”
Section: Discussionmentioning
confidence: 99%